Portfolio practices in the principal evaluation process: A qualitative case study - Ahmed Mohammed Alkaabi; Asma Khaleel Abdallah (Heliyon)
Background: The portfolio is a vital component of the evaluation of principals and serves as a repository of evidence of achievements, skills, and capabilities. It facilitates the meticulous recording and documentation of experiences undertaken. Furthermore, the portfolio is instrumental in the refinement of conceptual ideas over time, while simultaneously offering a panoramic vista of a school's operational ethos and its alignment with professional benchmarks. Objective: This study delves into the practices surrounding the principal portfolio and the formative and summative evaluation of principals by their evaluating supervisors. It aims to uncover principals’ perceptions regarding the obligatory nature of portfolios and other evaluative methodologies throughout both assessments. In light of the pivotal role that portfolios occupy in the realm of professional development and evaluation for school principals, the Abu Dhabi Education Council has mandated the compilation of principal portfolios within public schools. This mandate requires a detailed accounting of principals' proficiencies, achievements, and developmental trajectories. Markedly, this exploration stands as one of a scant number of inquiries probing the application of portfolios by school principals, with a particular focus on the context of the United Arab Emirates. It is poised to enrich the discourse on the utility of portfolios as instrumental tools for fostering leadership acumen and evaluative competency within the spheres of educator and principal preparation over the preceding two decades. The critical examination of these practices is vital for a nuanced understanding of their operational dynamics, the efficacy and challenges of e-portfolios, the array of opportunities they unveil, the identities of the involved stakeholders, and their ultimate objectives. Methods: This study adopted a qualitative research approach to gather and analyze non-numerical data in the form of concepts, opinions, and experiences presented by principals and their supervisors within the Al-Ain School District (overseen by the Abu Dhabi Education Council)). The cohort of participants comprised nine individuals endowed with extensive portfolio experience, six principals and three cluster managers. All worked in public educational institutions and were meticulously selected based on predefined criteria. This study relied on several data collection methods to obtain participants’ perspectives on their experiences with portfolio practices, including face-to-face interviews and documents from their portfolios. Results: A thematic analysis of the participant data yielded five salient themes reflecting the experiences of the principals: (1) inconsistent expectations for portfolio evidence; (2) portfolios summoned in response to rising tensions at the summative evaluation; (3) portfolios promoting reflective practices in formative evaluation; (4) portfolios susceptible to manipulation or falsification; and (5) excessive time spent building and developing portfolios. In order to maximize the utility of portfolios, this result invites school principals to unleash the latent potential inherent in their actions by leveraging portfolios as mirrors for reflective leadership and ongoing self-assessment. Conclusions: This research delineates both practical and theoretical ramifications for the application of professional portfolios. It elucidates the nature of evidence principals ought to incorporate within their portfolios. Furthermore, it endeavors to better inform principals of the evidence collection process, including what artifacts and documentation to gather and how to do so.